2022
DOI: 10.1093/europace/euac256
|View full text |Cite
|
Sign up to set email alerts
|

Scar border zone mass and presence of border zone channels assessed with cardiac magnetic resonance imaging are associated with ventricular arrhythmia in patients with ST-segment elevation myocardial infarction

Abstract: Aims Late gadolinium enhancement cardiac magnetic resonance (CMR) permits characterization of left ventricular ischaemic scars. We aimed to evaluate if scar core mass, border zone (BZ) mass, and BZ channels are risk markers for subsequent ventricular arrhythmia (VA) in ST-segment elevation myocardial infarction (STEMI). Methods and results A sub-study of the DANish Acute Myocardial Infarction-3 multi-centre trial and Danegapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…We hypothesize that our observations can be explained by more complex substrate which limits RFCA efficiency, especially in ES acute settings. In the presence of CTOs, scar border-zone (BZ) area is usually expected to be larger and more heterogenous ( 6 ) which strongly correlates with both spontaneous incident VTs ( 17 ) and VT inducibility at PVS ( 18 ). Most myocardial segments which are supplied by NR-CTOs have less than 50% scar transmurality ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that our observations can be explained by more complex substrate which limits RFCA efficiency, especially in ES acute settings. In the presence of CTOs, scar border-zone (BZ) area is usually expected to be larger and more heterogenous ( 6 ) which strongly correlates with both spontaneous incident VTs ( 17 ) and VT inducibility at PVS ( 18 ). Most myocardial segments which are supplied by NR-CTOs have less than 50% scar transmurality ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, myocardial fibrosis in the non-infarcted territory may have significant clinical consequences and be associated with reduced myocardial function. The peri-infarct zone is a determinant of ventricular arrhythmia 19, 20 . TPM-based assessment may, therefore, potentially be used to assess the risk of arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…The mass of the BZ and the amount and mass of BZ corridors have been strongly associated with VA and were reduced in the Sac/Val group. 31,32 In fact, efforts are being made to integrate these variables into prognostic algorithms. [33][34][35] In our study, the observed reductions in BZ mass and corridors in the Sac/Val group could potentially explain the reduction in inducible VT, as animals with inducible VT had greater BZ mass and BZ corridor numbers, regardless of the treatment received.…”
Section: Favorable Scar Remodelingmentioning
confidence: 99%